MENINGKATKAN PSYCHOLOGICAL WELL-BEING MELALUI CINEMA EDUCATION SEBAGAI UPAYA MENGHADAPI AGING POPULATION - Rahmaniar Rizky; Tyas Martika Anggriana; Noviyanti Kartika Dewi (Counsenesia Indonesian Journal Of Guidance and Counseling, 2020)
Psychological well-being is a condition where individuals can balance their potential optimally. The purpose of this was to determine whether there was an increase in psychological well-being before and after being given treatment as a preventive to face the aging population in Mangkujayan Village, Ponorogo District, Ponorogo Regency. The research design in this study was a one-group pretest-post test. The sampling technique of this research is purposive sampling. This sampling is done with the aim that there is no sample selection on the subject based on things outside the data needs of the study. The data collection technique used in this research is questionnaire, which is a data collection instrument that contains statements or questions which are then filled in by the respondent. The data analysis techniques using Wilcoxon Test through the SPSS 16 application. The results through the Wilcoxon Test show significant <0.05, namely 0.005 and it can be said that the hypothesis is accepted so that cinema education services can improve psychological well-being as a preventive effort to face the aging population in Mangkujayan Village, Ponorogo District, Ponorogo Regency in 2020.